Current Developments in the Financing of Offshore Wind Farms - Marita Balks; Lukas Mann (Wirtschaftsdienst)
Abstract Offshore wind farms are one of the most important pillars for the successful implementation of the energy transition. Worldwide, the expansion and development of these sustainable technologies is booming with different national challenges. What all projects have in common, however, is that a lot of capital is needed, and the trend is upward. For the financing of offshore wind farms, project financing has become increasingly established in Europe in recent years, but the contractual conditions have changed considerably. The current developments of financing structures for the realization of European offshore wind farms are shown on the basis of qualitative expert interviews.